Analisis Mutu Pelayanan Asuhan Gizi di Rawat Inap RSUP Prof. Dr. R. D. Kandou Manado - Nora Poluan; Nova H. Kapantow; Aaltje E. Manampiring (Universitas Sam Ratulangi, 2024)
Abstract: The success of standardized nutrition care process (PAGT) is determined by the effectiveness of nutrition interventions through effective education and counseling, providing appropriate dietetics for patients in hospitals, and collaboration with other professions greatly influences the success of PAGT. This study aimed to analyze the quality of nutrition care services in the inpatient care of Prof. Dr. R. D. Kandou Hospital Manado. This was a qualitative descriptive study using in-depth interview techniques and document review with seven informants. The data analysis process used an interactive analysis model of Miles and Huberman. The results showed that the services at Prof. Dr. R. D. Kandou Hospital Manado had already a policy referring to rules, Permenkes, and highest policies. Standardized Nutrition Care Process Guidelines by the Ministry of Health of the Republic of Indonesia 2014, and Hospital Nutrition Services (PGRS) of the Republic of Indonesia Ministry of Health 2013 were references for nutrition care services which must be updated continuously. Nutrition services to patients was good but not yet in accordance with the expected dietary requirements. Nutrition care services related to nutrition education to patients were good and were in line with patient expectations. The quality of nutritionists at Prof. Dr. R.D. Kandou Hospital Manado was good in knowledge and skills. In conclusion, the quality of service is an important thing that has to be up-dated continuously. Most of the nutritionists as nutrition care providers, are working in discipline and on time in service. However, in carrying out the standardized nutrition care process, errors were still found in filling out the integrated patient progress notes. Keywords: quality of service at the hospital; nutrition care; standardized nutrition care process Abstrak: Keberhasilan proses asuhan gizi terstandar (PAGT) ditentukan oleh efektivitas intervensi gizi melalui edukasi dan konseling yang efektif, pemberian dietetik sesuai untuk pasien di rumah sakit, dan kolaborasi dengan profesi lain. Penelitian ini bertujuan untuk menganalisis mutu pelayanan asuhan gizi di rawat inap RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif kualitatif dengan menggunakan tehnik wawancara mendalam dan telaah dokumen dengan jumlah tujuh informan. Proses analisis data dalam penelitian ini menggunakan model analisis interaktif Miles dan Huberman. Hasil penelitian mendapatkan bahwa pelayanan di RSUP Prof. Dr. R. D. Kandou Manado telah memiliki kebijakan yang mengacu pada aturan–aturan, permenkes, dan kebijakan-kebijakan tertinggi. Pelayanan Pedoman Proses Asuhan Gizi terstandar oleh Kemenkes RI 2014 dan Pelayanan Gizi Rumah Sakit (PGRS) Kemenkes RI 2013 menjadi acuan untuk Pelayanan Asuhan Gizi yang harus setiap waktu dikembangkan. Pelayanan gizi kepada pasien sudah baik tetapi belum sesuai dengan syarat diet yang diharapkan. Pelayanan asuhan gizi terkait edukasi gizi kepada pasien sudah baik dan sudah sesuai dengan harapan pasien. Kualitas ahli gizi di RSUP Prof. Dr. R. D. Kandou Manado sudah baik dalam pengetahuan dan keterampilan. Simpulan penelitian ini ialah mutu pelayanan asuhan gizi ialah hal penting yang harus terus diperbaharui. Sebagian besar ahli gizi sebagai pemberi asuhan gizi sudah baik dalam bekerja baik dalam disiplin, dan tepat waktu dalam pelayanan. Dalam pelakasanaan proses asuhan gizi terstandar masih ditemukan kesalahan dalam pengisian catatan perkembangan pasien terintegrasi Kata kunci: mutu pelayanan gizi di rumah sakit; asuhan gizi; proses asuhan gizi terstandar